Comparison of efficiency of healthcare systems of countries with global competitiveness using data envelopment analysis - Donhee Lee (Global Business & Finance Review (GBFR), 2016)
The purpose of this study is to evaluate and compare the efficiency of healthcare systems among 28 countries around the world by applying the data envelopment analysis (DEA) method. Two output variables are used: life expectancy at birth and infant mortality rate. Four input variables are used: number of physicians, number of hospital beds, radiotherapy units per million of the population, and total health expenditure as a percentage of the country's GDP. Using the DEA method, we evaluate how healthcare systems could set service levels in accordance with their strategic purpose or operational characteristics. This study contributes to the practice of healthcare management and could theoretically improve operational efficiency in the healthcare industry based on the compared efficiency of various healthcare systems.
Keywords: 650; Healthcare System; Efficiency; Data Envelopment Analysis; Global Competitiveness Country